Find the LCM of x^2y , xy^2 , and y^3

The LCM of x^2y, xy^2, and y^3 is x^2y^3.

Question

Asked 12/18/2014 6:49:56 PM

Updated 1/10/2015 2:04:08 PM

1 Answer/Comment

Rating

3

The LCM of x^2y, xy^2, and y^3 is x^2y^3.

Added 1/10/2015 2:04:08 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [1/10/2015 2:08:03 PM]

true or false, belief in Darwinism led persons to doubt that man owes anything to God. **Weegy:** TRUE - belief in Darwinism led persons to doubt that man owes anything to God.
(More)

Question

Expert Answered

Updated 12/12/2014 11:22:32 AM

0 Answers/Comments

-14 - (-13) - | 4 - 10 |?

Question

Updated 12/15/2014 6:27:33 AM

1 Answer/Comment

-14 - (-13) - | 4 - 10 |

= -14 + 13 - | -6 |

= -14 + 13 - 6

= -7

= -14 + 13 - | -6 |

= -14 + 13 - 6

= -7

Added 12/15/2014 6:27:33 AM

This answer has been confirmed as correct and helpful.

Write one of the factors of 100 **Weegy:** What about factors? **User:** Write one factor of 100 **Weegy:** In economics, factors of production, resources, or inputs are what is utilized in the production process in order to produce output that is, finished goods. **User:** The ratio of Hems to Haws was 9 to 3. If a total of 108 were present, how many of them were Hems? (More)

Question

Not Answered

Updated 12/17/2014 8:13:35 AM

1 Answer/Comment

Solve: (for x) w- 5y = x + y

Question

Updated 12/21/2014 8:44:10 PM

1 Answer/Comment

w- 5y = x + y

w - 5y - y = x

w - 6y = x

x = w - 6y

w - 5y - y = x

w - 6y = x

x = w - 6y

Added 12/21/2014 8:44:10 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [12/22/2014 7:13:44 AM]

{2x - y = -1 User: {2x - y = -1
{x + 3y = -11 (Use subscription.)
**Weegy:** 2x - 3y = 1,y = x -1 is equal to x = 2, y = 1.
**User:** what is the overall average of 90, 90, 90, 90, 82, and 82 (More)

Question

Updated 12/25/2014 12:19:35 AM

2 Answers/Comments

2x - y = -1 , y = 2x + 1

x + 3y = -11

x + 3(2x + 1) = -11

x + 6x + 3 = -11

7x = -14

x = -2

y = 2*(-2) + 1

y = -3

So the solution for 2x - y = -1 , y = 2x + 1 is x = -2, y = -3 .

x + 3y = -11

x + 3(2x + 1) = -11

x + 6x + 3 = -11

7x = -14

x = -2

y = 2*(-2) + 1

y = -3

So the solution for 2x - y = -1 , y = 2x + 1 is x = -2, y = -3 .

Added 12/25/2014 12:15:25 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [12/25/2014 1:15:55 PM]

The overall average of 90, 90, 90, 90, 82, and 82 is 87 1/3.

average = (90*4 + 82 + 82)/6 = 524/6 = 87 1/3.

average = (90*4 + 82 + 82)/6 = 524/6 = 87 1/3.

Added 12/25/2014 12:19:35 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [12/25/2014 1:17:25 PM]

29,524,602

questions answered

There are no comments.